2011
DOI: 10.1089/jwh.2009.1851
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Against a Link Between Hyperemesis Gravidarum and Personality Characteristics from an Ethnically Diverse Sample of Pregnant Women: A Pilot Study

Abstract: Background: Hyperemesis gravidarum (HG), a pregnancy-related condition marked by extreme nausea and vomiting, has been considered a psychosomatic illness associated with long-standing personality characteristics (e.g., hysteria). In this pilot study, we examined personality, somatic, and psychological variables with ethnically diverse samples of women with HG and women with typical levels of nausea and vomiting of pregnancy (NVP). Methods: Personality (Minnesota Multiphasic Personality Index-2 [MMPI-2] and MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Although the relationship between HG and psychiatric disorders has been examined, no consensus on this issue has been reached. Despite the few studies showing that HG is not a risk factor for antenatal depression or other psychosomatic disorders (33)(34), the general view is that the risk for antenatal depression increases in females with NVP, particularly in severe cases, which is consistent with our results. King et al examined 120 pregnant females and found significantly higher depression scores in those with HG than in a control group (35).…”
Section: A N U S C R I P Tsupporting
confidence: 90%
“…Although the relationship between HG and psychiatric disorders has been examined, no consensus on this issue has been reached. Despite the few studies showing that HG is not a risk factor for antenatal depression or other psychosomatic disorders (33)(34), the general view is that the risk for antenatal depression increases in females with NVP, particularly in severe cases, which is consistent with our results. King et al examined 120 pregnant females and found significantly higher depression scores in those with HG than in a control group (35).…”
Section: A N U S C R I P Tsupporting
confidence: 90%
“…This clinical status has been reported in 0.3-0.5% of all live births (1,2). The etiology of HG is unknown; however, hormonal, metabolic, neurotic, and psychosomatic disorders are thought to be the etiological factors (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…These may reflect more severe NVP symptoms due to less effective treatment. Depression by itself has not been shown to increase the likelihood of more common or more severe NVP [28] and headaches are not uncommon in severe forms of NVP. The significantly longer time till resolution of NVP in the control group and their higher likelihood of HG as compared to their previous pregnancy are consistent with our findings of lower quality of life among women with higher PUQE scores.…”
Section: Discussionmentioning
confidence: 99%